Review of Multiple Input Multiple Output Causal Strategies for Gene Selection - Ranny Ranny (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2011)
Feature extraction is one of a problem in bioinformatics. Bioinformatics research using many feature in their dataset. In this research we develop a method to find the interaction of the feature in the dataset. The method using multiple input and multiple output (MIMO) to select the feature of gene. The purpose of the experiment is to measure the effective and correctness of the MIMO method. The breast cancer dataset was used in the experiment. The result of the experiment show that the MIMO can improve the gene selection as the feature. Index Terms—Bioinformatics, breast cancer dataset, gene selection.